MY GUMMY DAN SOESANG MILK: TREN PEMANFAATAN SUSU DAN BUAH LOKAL SEBAGAI INOVASI GUNA MENDONGKRAK UMKM - Prapanca, Detak; Musyarofah, Sitta Rifatul; Maharani R.A, Viola; Sabela, Eka; Ismi W, Melly Wanda (Jurnal Abdi Masyarakat, 2024)
Gendro is a village in Pasuruan, East Java, which is rich in dairy milk potential and local fruits such as oranges. Through this potential, the KKN-P group consisting of 69 UMSIDA students innovated to develop products made from milk and oranges which became the flagship of Gendro village in the form of orange jelly candy branded "My Gummy" and banana milk branded "Soesang Milk". Both products are produced through research, interviews, and repeated trials to produce satisfactory final results. "My Gummy" and “Soesang Milk" products are packaged with attractive packaging and labels. Marketing of "My Gummy" and "Soesang Milk" products is carried out through social media and Gendro village folk party events on Sunday, March 3, 2024. The innovation of making "Soesang Milk" and "My Gummy" products is a positive step to develop and boost the economic conditions and competitiveness of MSMEs in Gendro village.